The perils of peer punishment: Evidence from a common pool resource experiment - Gioia de Melo; Matías Piaggio (Banco de México, 2015)
We provide experimental evidence on the effects of social disapproval by peers among communities of Uruguayan small-scale fishers exploiting a common pool resource (CPR). We combined this treatment with an in-group (groups from a single community) / mixed group (groups composed of fishers from different communities) treatment. We find that mixed groups, unlike in-groups, reduce their exploitation of the resource in response to the threat of punishment. Both in in-groups and mixed groups there is substantial antisocial punishment, which leads to increased extraction of the CPR by those who are unfairly punished. These findings indicate that effective peer punishment requires coordination to prevent antisocial targeting and to clarify the social signal conveyed by punishment.
Keywords: D03; O12; C93; 330; social disapproval; social preferences; common pool resource; desaprobación social; preferencias sociales; recurso de uso común